Hobson's choice - Lean, David, 1908-; Laughton, Charles, 1899-1962.; Mills, John, 1908-; British Lion Film Corp. Ltd.; Thorn EMI Video (Firm) ([New York, N. Y.] : Thorn EMI Video, 1954)
In the 1890's a tyrannical Lancashire bootmaker is brought to heel by his plain-speaking daughter and her simple-minded husband.
VHS format.
Editor, Peter Taylor ; music, Malcolm Arnold.
Charles Laughton, John Mills, Brenda de Banzie.
Keywords: Feature films